2018
DOI: 10.3390/ijms19092828
|View full text |Cite
|
Sign up to set email alerts
|

MT-Feeding-Induced Impermanent Sex Reversal in the Orange-Spotted Grouper during Sex Differentiation

Abstract: In this study, we systematically investigated the process of sex reversal induced by 17-methyltestosterone (MT) feeding and MT-feeding withdrawal at the ovary differentiation stage in orange-spotted groupers, Epinephelus coioides. Gonadal histology showed that MT feeding induced a precocious sex reversal from immature ovaries to testes, bypassing the formation of an ovarian cavity, and MT-feeding withdrawal led to an ovarian fate. In both the MT feeding and MT-feeding withdrawal phases, cytochrome P450 family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…DMRT1-positive signals were firstly detected in spermatogonia around the efferent duct; later, spermatocytes were evident. These results were similar to our previous study in which sex reversal was induced by MT or MT+E2 (39). In MT- or [MT+E2]-induced female-to-male sex reversal, the DMRT1-positive signals were firstly detected in cells around the efferent duct, and then spermatogonia and spermatocytes became evident.…”
Section: Discussionsupporting
confidence: 92%
“…DMRT1-positive signals were firstly detected in spermatogonia around the efferent duct; later, spermatocytes were evident. These results were similar to our previous study in which sex reversal was induced by MT or MT+E2 (39). In MT- or [MT+E2]-induced female-to-male sex reversal, the DMRT1-positive signals were firstly detected in cells around the efferent duct, and then spermatogonia and spermatocytes became evident.…”
Section: Discussionsupporting
confidence: 92%
“…japonica [ 17 ], Centropomus undecimalis [ 29 ], P. parva [ 18 ], and E . coioides [ 30 ]. The results of this study showed that MT disrupts the levels of GnRH and gonadotropins (LH and FSH); all three hormones increased and then decreased with increasing concentrations in female G .…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, exogenous hormones, such as estradiol and methyltestosterone, were observed to induce sex reversal in some aquatic animals [ 38 , 39 , 40 ]. Sex reversal represents an awesome sexual plasticity during the organism’s life cycle and triggers reproduction in animals [ 41 ].…”
Section: Discussionmentioning
confidence: 99%